A comparison of various machine learning approaches performance for prediction suspended sediment load of river systems: a case study in Malaysia - Hanoon M.S.; Abdullatif B A.A.; Ahmed A.N.; Razzaq A.; Birima A.H.; El-Shafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
comparative study; machine learning; river system; sensitivity analysis; suspended load; suspended sediment; water resource; Johor; Johor River; Krakatau; Lampung; Malaysia; Panjang; West Malaysia